IMPLEMENTATION OF FULL STACK WEB DEVELOPMENT FOR DATA ADMIN ON SOCIAL MEDIA BUZZBUDDIES - Humdiana Humdiana; Julieca Julieca (International Journal of Social Science, 2022)
Now, the internet and mobile phone technology is getting more advanced then social media also grows rapidly. In the dependence of human needs on social media and the rapid development of technology is making the number of new social media applications that appear in virtual worlds such as social media Buzzbuddies. This research is motivated by the difficulty of how Data Admin Buzzbuddies manage, organize data on social media Buzzbuddies and still depend on Backend Programmer which takes longer time. In addition, there is no report of available user data. This research use PostgreSQL for the database, AngularJs for client-side framework, Node.js for a server-side platform and Express for a server-side web application framework. This technology works together well as a stack. The purpose of this research is to make application can improve the effectiveness, reduce the work load and time and make the best of performance. In addition, the application is also able to provide data for analysis and decision support and able to manage data rationally